Hallo Pemberdayaan Masyarakat Melalui Tari Indang Di Nagari Paritmalintang, Kecamatan Enam Lingkung, Kabupaten Padang Pariaman, Sumatera Barat - Iza elvira salman (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2022)
Indang dance is a form of culture that still exists today and must be preserved. Indang dance is also known as dindin badindin. Indang dance is a traditional dance typical of the people of West Sumatra, especially Pariaman. At the beginning of the appearance of the Indang dance, which was spread by Sheikh Burhanuddin in the 13th or 14th century, it was used to spread the religion of Islam, but along with the development of the times, Indang dance did not only become a culture, but also as a performing art in the community, including the people of Nagari Paritmalintang.